Osteoporosis in Parkinson’s disease and the role of lean body mass: a cross-sectional study in a Brazilian tertiary center - Lima, Danielle Pessoa; Chagas-Neto, Francisco Abaeté das; Gomes de Luna, João Rafael; Martins, Yasmin de Oliveira; de Almeida, Samuel Brito; Feitosa, Camila Ximenes; Gradvohl, Leticia Brasil; Rosa, Isabele Dantas; Lopes, Fábia Karine de Moura; Aragão, Luciana Felipe Férrer; Viana-Júnior, Antonio Brazil; Augusto, Kristopherson Lustosa; et al. (Frontiers in Endocrinology, 2024)
Background: Parkinson's disease (PD) is the second most common neurodegenerative illness and has the highest increase rate in recent years. There is growing evidence to suggest that PD is linked to higher osteoporosis rates and risk of fractures.Objective: This study aims to estimate the prevalence and factors associated with osteoporosis as defined by the National Osteoporosis Foundation (NOF) and World Health Organization in patients with mild to moderate PD. Methods: We performed a cross-sectional study at a tertiary public hospital in Fortaleza, Brazil, dating from May 2021 until April 2022. The study sample was comprised of patients with mild to moderate PD who were at least 40 years old and who had the ability to walk and stand unassisted. Bone Mineral Density (BMD) of both the hip (neck of the femur) and the lumbar spine were obtained via properly calibrated Dual Energy X-ray Absorptiometry (DXA) scanning. The FRAX (Fracture Risk Assessment Tool) score was used to determine a person's 10-year risk of major osteoporotic fracture. The Revised European Working Group on Sarcopenia in Older People (EWGSOP 2) was used as a basis to confirm a sarcopenia diagnosis with the following parameters: low muscle strength gauged by handgrip strength and low muscle quantity by DXA. Physical performance was carefully evaluated by using the Short Physical Performance Battery test. Osteoporosis and osteopenia were diagnosed following the NOF guidelines and WHO recommendations. Results: We evaluated 107 patients in total, of whom 45 (42%) were women. The group's mean age was 68 ± 9 years, and the mean disease time span was 9.9 ± 6.0 years and mean motor UPDRS was 43 ± 15. We found that 42.1% and 34.6% of the sample had osteopenia and osteoporosis following NOF criteria, respectively, and 43% and 33.6% following the WHO recommendations. Lower lean appendicular mass was associated to osteopenia and osteoporosis in multinomial logistic regression analysis in both diagnostic criteria. Conclusion: Our findings provide additional evidence for the protective role of lean mass against osteoporosis in patients with PD.